Pengaruh Teknologi Informasi dan Kualitas Audit Terhadap Keandalan Laporan Keuangan: Studi Empiris Sektor Keuangan di Alor Nusa Tenggara Timur - Risma Ernilamsari; Aris Eddy Sarwono; Sinta Putriana (Lembaga Teewan Journal Solutions, 2026)
The reliability of financial reports is a critical requirement for stakeholders, yet its achievement remains a challenge in Alor Regency. This study examines the effect of information technology and audit quality on financial report reliability, both partially and simultaneously, across public and private sectors in Alor Regency. Data were collected through questionnaires from 68 respondents selected via purposive sampling, comprising accounting staff, auditors, treasurers, and managers. Multiple linear regression was used for analysis after classical assumption tests were fulfilled. Results indicate that information technology has no significant partial effect on financial report reliability (sig. 0.102), while audit quality has a positive and significant partial effect (sig. 0.000; coefficient 0.666) as the most dominant variable. Simultaneously, both variables produce a significant effect with an F-value of 50.746, explaining 59.8% of the variation in financial report reliability. This study concludes that strengthening audit functions and improving information technology capacity must be carried out together to enhance financial report reliability in Alor Regency.